2015
DOI: 10.1371/journal.pone.0128063
|View full text |Cite
|
Sign up to set email alerts
|

Encounter Decision Aid vs. Clinical Decision Support or Usual Care to Support Patient-Centered Treatment Decisions in Osteoporosis: The Osteoporosis Choice Randomized Trial II

Abstract: PurposeOsteoporosis Choice, an encounter decision aid, can engage patients and clinicians in shared decision making about osteoporosis treatment. Its effectiveness compared to the routine provision to clinicians of the patient’s estimated risk of fracture using the FRAX calculator is unknown.MethodsPatient-level, randomized, three-arm trial enrolling women over 50 with osteopenia or osteoporosis eligible for treatment with bisphosphonates, where the use of Osteoporosis Choice was compared to FRAX only and to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 18 publications
0
109
0
1
Order By: Relevance
“…Three studies assessed helpfulness of the information in the intervention and control group. Results from all studies indicated that clinicians found the information in the decision aid group more helpful than in the control (mean difference 0.64, 95% CI 0.18 to 1.0927 (table 2); 70% vs 35% of clinicians judged information as helpful26 and a significantly higher proportion (54.1%) of clinicians in the intervention group who judged the information as extremely helpful compared with the control (33.7%) (figure 2). 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies assessed helpfulness of the information in the intervention and control group. Results from all studies indicated that clinicians found the information in the decision aid group more helpful than in the control (mean difference 0.64, 95% CI 0.18 to 1.0927 (table 2); 70% vs 35% of clinicians judged information as helpful26 and a significantly higher proportion (54.1%) of clinicians in the intervention group who judged the information as extremely helpful compared with the control (33.7%) (figure 2). 15…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five papers met the inclusion criteria including 22 RCTs and 3 qualitative or mixed-methods studies nested in an RCT, together representing 23 unique trials (online supplementary file 1). 13–37 One study was excluded because it had no comparator group without decision aid 38. There were three nested qualitative studies and nine RCTs included in our review that were not included in the Cochrane review, the majority of which were published after April 2015, the date of the literature search for the Cochrane review.…”
Section: Resultsmentioning
confidence: 99%
“…The FRAX (Fracture Risk Assessment Tool) score was also not incorporated in the analysis due to the absence of data. Knowledge of the risk of a new fracture could potentially influence patient preferences [36].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Recordings were audiovisual or audio-only based on the preferences of the patients and their clinicians at the time of enrollment. Of the 272 complete videos available for analyses from these trials, we included all the videos that were recorded in specialty care (51) and selected a random sample of 61 videos from the 221 remaining primary care videos stratified by treatment arm (decision aid use) to complete a sample of 112 videos.…”
Section: Methodsmentioning
confidence: 99%